Effectiveness of genetic cascade screening for familial hypercholesterolaemia using a centrally co-ordinated clinical service: An Australian experience. Issue 1 (March 2015) - Bell, Damon A.; Pang, Jing; Burrows, Sally; Bates, Timothy R.; van Bockxmeer, Frank M.; Hooper, Amanda J.; O'Leary, Peter; Burnett, John R.; Watts, Gerald F.
Abstract Background Familial hypercholesterolaemia (FH) is a co-dominantly inherited disorder of low-density lipoprotein (LDL) catabolism, causing elevated LDL-cholesterol and premature coronary artery disease (CAD). Several guidelines recommend genetic cascade screening relatives of probands (index cases) with genetically proven FH, but experience in a clinical service setting is limited. Methods Relatives from 100 index cases with genetically confirmed FH underwent genetic and lipid testing via a centralised screening program in Western Australia. The program's effectiveness was evaluated as the number of newly diagnosed relatives with FH per index case and the proportional reduction in LDL-cholesterol after treatment. Results Of 366 relatives tested for FH, 188 (51.4%) were found to have a pathogenic mutation. On average, 2 cases were detected per index case. Affected relatives were younger and less likely to have physical stigmata of FH and premature CAD than index cases (p < 0.001). Of the new cases, 12.8% had hypertension, 2.7% had diabetes and 16.0% were smokers; 48.4% were already on statin therapy and these were older (p < 0.001) and had more vascular risk factors and CAD (p < 0.01) than those not on therapy. Significant reductions in LDL-cholesterol (−24.3%, p < 0.001) were achieved overall, with previously untreated new cases of FH attaining a maximal average reduction of 42.5% in LDL-cholesterol after drug therapy. Over 90% of subjects were satisfied with screening and care. Conclusion Genetic cascade screening co-ordinated by a centralised service is an effective and acceptable strategy for detecting FH in an Australian setting. A significant proportion of new cases exhibit other CAD risk factors and are already on statins, but have not received a prior diagnosis of FH.